2008
DOI: 10.1029/2007jg000501
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of rice methane emission by sulfate deposition in simulated acid rain

Abstract: [1] Sulfate in acid rain is known to suppress methane (CH 4 ) emissions from natural freshwater wetlands. Here we examine the possibility that CH 4 emissions from rice agriculture may be similarly affected by acid rain, a major and increasing pollution problem in Asia. Our findings suggest that acid rain rates of SO 4 2À deposition may help to reduce CH 4 emissions from rice agriculture. Emissions from rice plants treated with simulated acid rain at levels of SO 4 2À consistent with the range of deposition in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…Natural emissions would be reduced under sulfate geoengineering for three main reasons: (1) a reduction in surface temperatures that would, in turn, be connected with a highly probable reduction in rainfall, compared with the predicted increase under most future warming scenarios (Trenberth, 1998;Pandey et al, 2017); this would reduce the amount of CH 4 produced by wetland areas, thus affecting the atmospheric methane concentration; (2) the increased surface deposition of sulfate under SG conditions would itself produce changes in emissions from wetlands (Gauci et al, 2008); (3) SG could help avert one of the possible risks of global warming, i.e., the emission of methane from permafrost thawing (Kohnert et al, 2017). It remains to be investigated how much these effects, together, could offset the photochemical CH 4 increase resulting from our study.…”
Section: Discussionmentioning
confidence: 99%
“…Natural emissions would be reduced under sulfate geoengineering for three main reasons: (1) a reduction in surface temperatures that would, in turn, be connected with a highly probable reduction in rainfall, compared with the predicted increase under most future warming scenarios (Trenberth, 1998;Pandey et al, 2017); this would reduce the amount of CH 4 produced by wetland areas, thus affecting the atmospheric methane concentration; (2) the increased surface deposition of sulfate under SG conditions would itself produce changes in emissions from wetlands (Gauci et al, 2008); (3) SG could help avert one of the possible risks of global warming, i.e., the emission of methane from permafrost thawing (Kohnert et al, 2017). It remains to be investigated how much these effects, together, could offset the photochemical CH 4 increase resulting from our study.…”
Section: Discussionmentioning
confidence: 99%
“…Driscoll et al, 2001) but the impact on the global carbon cycle has not been quantified. Sulphate deposition also impacts natural wetlands and rice paddies resulting in suppressed methane emissions (Gauci et al, 2008). The future deposition of particulates to ecosystems will depend on both changes to anthropogenic emissions and climate (e.g., Tagaris et al, 2008).…”
Section: Natural Aerosols As a Source Of Nutrients For Vegetationmentioning
confidence: 99%
“…The artificial method eradicating methane emission from acid rain formation [5] is parallel to give poison to someone to eradicate another poison. In the artificial acid rain formation the boundary cannot be fixed due to reasons described in the introduction part of the manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…Gauci et al [5] found that acid rain rates of SO 4 2-deposition may help reduce CH 4 emissions from paddy fields. Emissions from rice plants treated with simulated acid rain at levels of SO 4 2-consistent with the range of deposition in Asia were reduced by 24% during the grain filling and ripening stage of the rice 4 emission by 43%.…”
Section: Beneficial Effect Of Acid Rain: a Contrary Viewmentioning
confidence: 99%